TEORI KEPEMIMPINAN: SEBUAH TINJAUAN DARI PERSPEKTIF FILSAFAT ILMU - Hening Riyadiningsih (SEGMEN Jurnal Manajemen dan Bisnis, 2016)
The purpose of this article is to describe the various positions of leadership theory from the perspective of Kierkegaard’s philosophy. Mode of existence of Kierkegaard’s philosophy consist of  mode of existence of aesthetics, mode of existence of ethical, and mode of existence of religion. The development of these three modes of existence has been following the process of development Ironic -Reflective. Based on linkage between mode of existence with the position of leadership theory, then there are three positions of leadership theory is the instrumental position, the position of responsibility, and spiritual position. The Position of instrumental leadership theory is based on mode of existence of aesthetics, viewed from the standpoint of mechanical. The position of responsibility leadership theory is based on the mode of existence of ethicals, which leadership  theory are viewed from the perspective of social responsibility, the environment, and officials, which is reflected in the activities that are based on the values ​​and norms of society and ecological. The position of spiritual leadership theory is based on the mode of existence of religious, viewed from the standpoint of organic. There is interdependence of all the elements that exist in the organization, because the organization is considered as a system of interconnected organism. From the perspective of the philosophy of Kierkegaard, in spiritual position, intuition is introduced as source of knowlwdge.. Keyword: Ontology, Epistemology, Axiology,  Mode of Existence of Kierkegaard Philosophy, Interpretation of Development Process Ironic-Reflective, Leadership Position of Instrumental, Leadership Position of Responsibility, and Leadership Position of Spiritual